2022
DOI: 10.1002/dac.5298
|View full text |Cite
|
Sign up to set email alerts
|

Statistical channel model to characterize turbulence‐induced fluctuations in the underwater wireless optical communication links

Abstract: Summary Underwater wireless optical communication (UWOC) turns out to be a primary sought alternative to wireless technology, which can provide high data rate, enormous bandwidth, and low deployment cost and resolve the crowded radio frequency band issues. The performance of the UWOC link is significantly affected by the turbulent ocean environment. In this paper, the different turbulence scenarios such as salinity gradients, temperature gradients, and air bubbles are considered to model the turbulent nature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A new turbulence channel model was proposed in [16], which excellently fitted with experimental data. The experimental results indicated that the proposed model is more suitable for describing oceanic turbulent environments for all considered turbulence scenarios.…”
Section: Uowc Systemmentioning
confidence: 99%
“…A new turbulence channel model was proposed in [16], which excellently fitted with experimental data. The experimental results indicated that the proposed model is more suitable for describing oceanic turbulent environments for all considered turbulence scenarios.…”
Section: Uowc Systemmentioning
confidence: 99%